PERAN WANITA ISLAM AL-KHAIRAAT DAN MASYARAKAT KELURAHAN LOLU UTARA DALAM MEWUJUDKAN NILAI TOLERANSI UMAT BERAGAMA DAN KEARIFAN LOKAL : (STUDI LIVING KITAB SUCI) - Yamani, Gasim; Sakinah, Sari (Comparativa: Jurnal Ilmiah Perbandingan Mazhab dan Hukum, 2025)
This study examines the practice of religious moderation and the preservation of local wisdom in Lolu Utara Subdistrict, Palu Timur District, Palu City, which is known for its ethnic and religious diversity yet maintains social harmony. The objective is to analyze the community’s religious activities that reflect the values of the Qur’an and the Bible in managing conflicts related to ethnicity, religion, race, and inter-group relations (SARA) through the Living Holy Book approach. This quantitative study uses proportional sampling techniques, with data collected through questionnaires, surveys, and interviews. The findings indicate a high level of tolerance among the people of Lolu Utara, supported by the active role of community leaders and Wanita Islam Al-Khairaat (WIA) in promoting moderation. Local wisdom, such as Nosarara Nosabatutu, further strengthens social harmony. Lolu Utara can serve as a model for successful community-based religious moderation.